The Design and Evaluation of a Portable Extracorporeal Centrifugal Blood Pump - Wu, Peng; Xiang, Wenjing; Yin, Chengke; Li, Shu (Frontiers in Physiology, 2021)
Blood pump is one of the core components of extracorporeal membrane oxygenation (ECMO), which can provide support for patients with COVID-19-related acute respiratory distress syndrome. Portability and wearability of blood pumps should be considered to ensure patient satisfaction in everyday life. To date, the focus has been on the development of portable and wearable peripheral components, little attention has been paid to the portable and wearable performance of the blood pump itself. This study reported a novel design of a wearable and portable extracorporeal centrifugal blood pump. Based on an in-house centrifugal maglev blood pump, the wearable and portable blood pump was designed with parallel inlet and outlet pipes to improve the wearable performance. A ring cavity was set at the inlet to convert the circumferential velocity of the inlet pipe to an axial velocity. The hydraulic and hemolytic performance of the baseline and portable blood pumps were analyzed and compared. Compared with the baseline pump, the hydrodynamic and hemolytic performance of the portable pump has been maintained without serious degradation. The results of this study will benefit the design of ECMO system, facilitate the life of COVID-19 patient, and contribute to more sustainable society and cities.